Making good things even better: regulatory impact assessment of the incentives regime in the environmental enforcement field - López Medrano, Gabriela (2016)
All regulatory activity from the administration has an impact on the market and on people’s actions. For this reason, it is necessary to have tools to predict and evaluate these impacts, so that the most efficient state measures are chosen, avoiding undesirable results.In this article, the authors emphasize the need for an ex post regulatory impact assessment to maintain the effectiveness of the regulatory instruments chosen. This, especially for new regulatory measures, such as the incentive scheme recently implemented by the OEFA.